ANALISIS RASIO KEUANGAN UNTUK MENEMUKAN BANK JANGKAR (STUDI PADA BANK UMUM SYARIAH DI INDONESIA) - Drs. Agus Sucipto, MM.,, Achmad Zainuri, SE (Fakultas Ekonomi, UIN Maliki Malang, 2007)
This research based on API, anchor bank, and the growth of syariah commercial bank (BUS). This research aims to description BUS financial ratio with documentary technic in collecting data. This research use secondary data in form of financial report. Instrument analysis is banking financial ratios with time series analysis and cross sectional approach as tekhnis analysis. The research shows that syariah commercial bank have potential to be an anchor bank, but PT. Bank Muamalat Indonesia have more potential according to his financial ratios.